Theoretical assumptions about family firm radical innovation - Qilin Hu; Mathew Hughes (2019)
Investigations of family firm radical innovation have diffused into various research streams driven primarily by governance. This has created a wide range of findings originating from a different set of theoretical assumptions whose implications for the accumulation of knowledge are unclear. This paper evaluates our understanding of family firm radical innovation using a structured literature review. Analysis of 41 seminal articles identifies four persistent theoretical lenses: (1) resources, (2) agency, (3) behavioural agency and socioemotional wealth, and (4) the ability and willingness to innovate. We present key problems needing urgent attention to advance our understanding of family firm radical innovation.